The Effect of Breath Relaxation Techniques on the Reduction of Pain Scale in Post Operating Laparatomic Patients in Space Al-Insan Room Hospital Linggau Lubuk City - Yati Rosmiati (Perkumpulan Dosen Muda Bengkulu, 2021)
Laparatomy is a surgical procedure that involves an incision in the abdominal wall into the abdominal cavity. Relaxation techniques are independent nursing interventions to reduce pain intensity, relaxation techniques provide individuals with self-control when pain occurs and can be used when someone is healthy or sick (Smlezer, 2012). The research problem is that there are still many postoperative laparotomy patients who complain of pain. The aim of the study is to influence the deep breath relaxation technique on reducing the pain scale of post-laparotomy postoperative patients in the Al-Insan Room, Siti Aisyah Hospital, Lubuk Linggau City. This study used a research method using a pre-experimental design with a research design (pre test and post test one group desaign) (Arikunto, 2010). Sampling with accidental sampling large sample of 12 people with characteristics that are close to. Data were analyzed univariately and bivariately displayed in the form of a frequency distribution table using the Shapiro Wilk normality test and statistical paired sample t test. The results of the study the average pain scale before 5.25 and after taking breath relaxation measures in the pain scale score of 3.67. The results of the Shapiro Wilk test p value 0.05 and the paried statistical test sample t test p value 0.000. Conclusion: Anxiety data before and after data therapy is normally distributed and there is an effect of deep breath relaxation techniques on reducing the pain scale in postoperative Laparatomy patients in the Al-Insan Room, Siti Aisyah Hospital, Lubuk Linggau City. The results of this study are expected to be used as motivation to maintain and improve health services as a whole, especially regarding pain intensity management using non-pharmacological techniques, namely deep breath relaxation techniques. It is hoped that it can increase knowledge and insight for nurses, as well as patient and family satisfaction in distraction techniques on pain intensity in postoperative patients.